FINAL REDOXIDATION OF COPPER AND BRONZE ALLOYS EXPERIMENTAL AND INDUSTRIAL ANALYSIS - Abdurafiqov Behzod Anvarjon o‘g‘li; Raximboyev Sherzodjon Ikrom o‘g‘li (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This thesis presents an experimental and industrial study of the final redoxidation of copper and bronze alloys. Oxygen pickup during reoxidation was measured under laboratory and industrial conditions. The effects of oxygen on microstructure, mechanical strength, and electrical conductivity were analyzed.